Photophysical and photochemical properties of newly synthesized zinc(II) and chloroindium(III)phthalocyanines substituted with 3,5-bis(trifluoromethyl)phenoxy groups - Ahmetali, Erem; Atmaca, Goknur Yasa; Karaoglu, Hande Pekbelgin; Erdogmus, Ali; Kocak, Makbule Burkut (WORLD SCI PUBL CO INC, 2019)
4,5-bis(3,5-bis(trifluoromethyl)phenoxy)phthalonitrile (1) and its complexes, namely 2,3,9,10,16,17,23,24-ocialcis[3,5-bis(trifluoromethyl)phenoxy] phthalocyaninato zinc(II) (2) and 2,3,9,10,16,17,23,24-octalds[3,5-bis(trifluoromethypphenoxy]phthalocyaninato indium(III) (3) are synthesized and characterized. Aggregation of the phthalocyanines was studied in tetrahydrofuran in different concentrations. Photochemical and photophysical properties of 2 and 3 in THF were investigated. A comparison between the photophysicochemical parameters of 2 and 3 yielded that 3 is a better photosensitizer than 2. The fluorescence quantum yields (Phi(F)) and O-1(2) formation (Phi(Delta)) for compound 3 are 0.016 and 0.84, respectively. The values for compound 2 are 0.135 and 0.54, respectively. The values of indium and zinc phthalocyanines (2 and 3) could be classified as photosensitizers in the photocatalytic applications such as photodynamic therapy (PDT) of cancer.
Keywords: zinc(II) phthalocyanine; chloroindium(III) phthalocyanine; photochemistry; photophysics; singlet oxygen; INDIUM(III) PHTHALOCYANINES; ANTIOXIDANT PROPERTIES; PHOTODYNAMIC THERAPY; AGGREGATION; GALLIUM; PHOTOSENSITIZER; FLUORESCENCE; DERIVATIVES; COMPLEXES; CHAIN; Chemistry